Nothing to lose eaudiobook - Child, Lee (Jack Reacher, 2008)
#1 NEW YORK TIMES BESTSELLER • Don’t miss the hit streaming series Reacher ! “Explosive and nearly impossible to put down.”— People Two small towns in the middle of nowhere: Hope and Despair. Between them, nothing but twelve miles of empty road. Jack Reacher can’t find a ride, so he walks. All he wants is a cup of coffee. What he gets are four hostile locals, a vagrancy charge, and an order to move on. They’re picking on the wrong guy. Reacher is a hard man. No job, no address, no baggage. Nothing at all, except hardheaded curiosity. What are the secrets that Despair seems so desperate to hide? With just one ally—a mysterious woman cop from Hope—and many enemies, Reacher goes up against a whole town, hunting the rich man at its core, cracking open his terrifying agenda, asking the question: Who has the edge—a man with everything to gain, or a man with nothing to lose?